Canopy gap age influences snow depth: Implications for gap-based silviculture on snowpack in the Sierra Nevada - Sabrina Chui; Tessa Maurer; Gregory Verutes; Matthew D. Potts; Robert York (Forest Ecology and Management, 2026)

PM2.5 infiltration from controlled burns in dwellings in a rural community within Mpumalanga, South Africa - Matthew Benyon; Daniel A. Potts; Ngwako Kwatala; Siyathemba Kunene; F. Xavier Gómez-Olivé; Samuel Cai; Caradee Y. Wright; Joshua D. Vande Hey (Atmospheric Environment, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Assessing land use change trajectories following food insecurity shocks in 25 low- and middle-income countries - Evan Patrick; Van Butsic; Matthew D. Potts (Global Environmental Change, 2025)

Quantifying the Effect Size of Management Actions on Aboveground Carbon Stocks in Forest Plantations - Cyril H. Melikov; Jacob J. Bukoski; Susan C. Cook-Patton; Hongyi Ban; Jessica L. Chen; Matthew D. Potts (Current Forestry Reports, 2023)
Purpose of the Review Improved forest management is a promising avenue for climate change mitigation. However, we lack synthetic understanding of how different management actions impact aboveground carbon stocks, particularly at scales relevant for designing and implementing forest-based climate solutions. Here, we quantitatively assess and review the impacts of three common practices—application of inorganic NPK fertilizer, interplanting with N-fixing species, and thinning—on aboveground carbon stocks in plantation forests. Recent Findings Site-level empirical studies show both positive and negative effects of inorganic fertilization, interplanting, and thinning on aboveground carbon stocks in plantation forests. Recent findings and the results of our analysis suggest that these effects are heavily moderated by factors such as species selection, precipitation, time since practice, soil moisture regime, and previous land use. Interplanting of N-fixing crops initially has no effect on carbon storage in main tree crops, but the effect becomes positive in older stands. Conversely, the application of NPK fertilizers increases aboveground carbon stocks, though the effect lessens with time. Moreover, increases in aboveground carbon stocks may be partially or completely offset by emissions from the application of inorganic fertilizer. Thinning results in a strong reduction of aboveground carbon stocks, though the effect lessens with time. Summary Management practices tend to have strong directional effects on aboveground carbon stocks in plantation forests but are moderated by site-specific management, climatic, and edaphic factors. The effect sizes quantified in our meta-analysis can serve as benchmarks for the design and scoping of improved forest management projects as forest-based climate solutions. Overall, management actions can enhance the climate mitigation potential of plantation forests, if performed with sufficient attention to the nuances of local conditions.

Memory over matter?—a conceptual framework to integrate social–ecological l legacies in agricultural NCP co-production - Julia Grosinger; Matthew D. Potts; Nicolas Buclet; Sandra Lavorel (Sustainability Science, 2022)
To better account for how social–ecological legacies of social and ecological systems jointly shape the current composition, the quality and quantity of nature’s contribution to people (NCPs), we integrate the concept of NCP co-production into social–ecological system thinking. Our expanded framework highlights how NCP co-production is frequently entangled within its social–ecological context, such as legacies, current resources and social activities. Additionally, we underline the relevance of non-material and material dimensions of resources in NCP co-production. To illustrate the potential of this expanded framework, we explore its application to an agricultural system of the French Northern Alps. We conclude that this framework (1) facilitates the understanding of society–ecosystem interactions in a specific regional social–ecological context; (2) helps to better conceptualise the interdependencies between resources and social activities; (3) demonstrates how current rule sets to organise social–ecological legacies affect the entire NCP co-production chain. The framework’s further implementation requires more research to better understand the complex interlinkages between the social and the ecological subsystems that underpin socioeconomic activities.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Richer histories for more relevant policies: 42 years of tree cover loss and gain in Southeast Sulawesi, Indonesia - Lisa C. Kelley; Samuel G. Evans; Matthew D. Potts (Global Change Biology, 2017)
Understandings of contemporary forest cover loss are critical for policy but have come at the expense of long‐term, multidirectional analyses of land cover change. This is a critical gap given (i) profound reconfigurations in land use and land control over the past several decades and (ii) evidence of widespread ‘woodland resurgence’ throughout the tropics. In this study, we argue that recent advancements within the field of land change science provide new opportunities to address this gap. In turn, we suggest that multidecadal and multidirectional analyses of land cover change can facilitate richer social analyses of land cover change and more relevant conservation policies and practice. Our argument is grounded in a case study from Southeast Sulawesi, Indonesia. Using a novel analytical platform, Google Earth Engine, and open access to high‐quality Landsat data, we map land cover change in Southeast Sulawesi, Indonesia, from 1972 to 2014. We find that tree cover loss constitutes the single largest net change over the period 1972–2014 but that gross rates of tree cover gain were three times higher than gross loss rates from 1972 to 1995 and equivalent to loss rates from 1995 to 2014. We suggest the smallholder tree crop economy likely produced both forest loss and Imperata grassland restoration in this region. This case points to the need to expand rather than collapse the baselines used to study carbon and biodiversity change in tropical regions. It also demonstrates the possible utility of applying such methods to other regions.

Assessing Mangrove Above-Ground Biomass and Structure using Terrestrial Laser Scanning: A Case Study in the Everglades National Park - Emanuelle A. Feliciano; Shimon Wdowinski; Matthew D. Potts (Wetlands, 2014)

Linking size‐dependent growth and mortality with architectural traits across 145 co‐occurring tropical tree species - Yoshiko Iida; Lourens Poorter; Frank Sterck; Abd Rahman Kassim; Matthew D. Potts; Takuya Kubo; Takashi S. Kohyama (Ecology, 2014)
Tree architecture, growth, and mortality change with increasing tree size and associated light conditions. To date, few studies have quantified how size‐dependent changes in growth and mortality rates co‐vary with architectural traits, and how such size‐dependent changes differ across species and possible light capture strategies. We applied a hierarchical Bayesian model to quantify size‐dependent changes in demographic rates and correlated demographic rates and architectural traits for 145 co‐occurring Malaysian rain‐forest tree species covering a wide range of tree sizes. Demographic rates were estimated using relative growth rate in stem diameter (RGR) and mortality rate as a function of stem diameter. Architectural traits examined were adult stature measured as the 95‐percentile of the maximum stem diameter (upper diameter), wood density, and three tree architectural variables: tree height, foliage height, and crown width. Correlations between demographic rates and architectural traits were examined for stem diameters ranging from 1 to 47 cm. As a result, RGR and mortality varied significantly with increasing stem diameter across species. At smaller stem diameters, RGR was higher for tall trees with wide crowns, large upper diameter, and low wood density. Increased mortality was associated with low wood density at small diameters, and associated with small upper diameter and wide crowns over a wide range of stem diameters. Positive correlations between RGR and mortality were found over the whole range of stem diameters, but they were significant only at small stem diameters. Associations between architectural traits and demographic rates were strongest at small stem diameters. In the dark understory of tropical rain forests, the limiting amount of light is likely to make the interspecific difference in the effects of functional traits on demography more clear. Demographic performance is therefore tightly linked with architectural traits such as adult stature, wood density, and capacity for horizontal crown expansion. The enhancement of a demographic trade‐off due to interspecific variation in functional traits in the understory helps to explain species coexistence in diverse rain forests.

Pseudoreplication in Tropical Forests and the Resulting Effects on Biodiversity Conservation - BENJAMIN S. RAMAGE; DOUGLAS SHEIL; HANNAH M.W. SALIM; CHRISTINE FLETCHER; NUR‐ZATI A. MUSTAFA; JOANN C. LURUTHUSAMAY; RHETT D. HARRISON; ELIZABETH BUTOD; AHMAD DZAMIR DZULKIPLY; ABD RAHMAN KASSIM; MATTHEW D. POTTS (Conservation Biology, 2013)
Tropical forest ecosystems are threatened by habitat conversion and other anthropogenic actions. Timber production forests can augment the conservation value of primary forest reserves, but studies of logging effects often yield contradictory findings and thus inhibit efforts to develop clear conservation strategies. We hypothesized that much of this variability reflects a common methodological flaw, simple pseudoreplication, that confounds logging effects with preexisting spatial variation. We reviewed recent studies of the effects of logging on biodiversity in tropical forests ( n = 77) and found that 68% were definitively pseudoreplicated while only 7% were definitively free of pseudoreplication. The remaining proportion could not be clearly categorized. In addition, we collected compositional data on 7 taxa in 24 primary forest research plots and systematically analyzed subsets of these plots to calculate the probability that a pseudoreplicated comparison would incorrectly identify a treatment effect. Rates of false inference (i.e., the spurious detection of a treatment effect) were >0.5 for 2 taxa, 0.3–0.5 for 2 taxa, and Pseudoreplicación en Bosques Tropicales y Efectos Resultantes Sobre la Conservación de Biodiversidad

Optimized Floating Refugia: a new strategy for species conservation in production forest landscapes - Benjamin S. Ramage; Justin Kitzes; Elaina C. Marshalek; Matthew D. Potts (Biodiversity and Conservation, 2013)

Habitat heterogeneity and niche structure of trees in two tropical rain forests - Matthew D. Potts; Stuart J. Davies; William H. Bossert; S. Tan; M. N. Nur Supardi (Oecologia, 2004)